Reproductive Aging Drives Protein Accumulation in the Uterus and Limits Lifespan in C. elegans. - Stephanie M Zimmerman; Izumi V Hinkson; Joshua E Elias; Stuart K Kim (PLoS Genetics)
Aging in Caenorhabditis elegans is characterized by widespread physiological and molecular changes, but the mechanisms that determine the rate at which these changes occur are not well understood. In this study, we identify a novel link between reproductive aging and somatic aging in C. elegans. By measuring global age-related changes in the proteome, we identify a previously uncharacterized group of secreted proteins in the adult uterus that dramatically increase in abundance with age. This accumulation is blunted in animals with an extended reproductive period and accelerated in sterile animals lacking a germline. Uterine proteins are not removed in old post-reproductive animals or in young vulvaless worms, indicating that egg-laying is necessary for their rapid removal in wild-type young animals. Together, these results suggest that age-induced infertility contributes to extracellular protein accumulation in the uterus with age. Finally, we show that knocking down multiple age-increased proteins simultaneously extends lifespan. These results provide a mechanistic example of how the cessation of reproduction contributes to detrimental changes in the soma, and demonstrate how the timing of reproductive decline can influence the rate of aging.